Conspicuous distinction: a reading of Veblen and Bourdieu - Guimarães, Isabel (2018)
The paper provides a comparative reading of two influential works of Veblen and Bourdieu, on cultural consumption. Approaches to consumers‟ taste and preferences are predominantly essentialist. However, Veblen and Bourdieu focused on the relationship between consumption and social divisions. Their views are, nonetheless, contrasting. Veblen developed a somewhat speculative approach centred on waste and conspicuous consumption as evidence for the natural quest for social honour. Bourdieu drew on empirical research to argue that culture stems from class and is related to necessity. The concepts of habitus, cultural capital and field interact to provide a complex and detailed account of different tastes emerging within different social classes. The result is a variegated social space with different statuses and an ongoing struggle for the definition of „good” and “bad” taste.